Confined La2O3 particles in mesoporous carbon material for enhanced phosphate adsorption. Issue 8 (4th August 2021) - Ju, Xiaoqiu; Cui, He; Liu, Tao; Sun, Yabing; Zheng, Shourong; Qu, Xiaolei
Abstract : Novel phosphate adsorbents with confined La2 O3 inside mesoporous carbon were fabricated by the solid-state grinding method using pristine mesoporous carbon material CMK-3 (PCMK-3) and oxidized CMK-3 (OCMK-3) as the matrixes (denoted as La2 O3 @PCMK-3 and La2 O3 @OCMK-3). Compared with pure La2 O3, La2 O3 @PCMK-3 and La2 O3 @OCMK-3 exhibited higher normalized phosphate adsorption capacity, indicative of efficient loading of La2 O3 inside the mesopores of the carbon materials. Furthermore, La2 O3 loading led to substantially enhanced phosphate adsorption. The adsorption capacities of La2 O3 @OCMK-3 samples were higher than those of La2 O3 @PCMK-3 samples, possibly owing to the oxygen-containing groups forming in OCMK-3 during HNO3 oxidation, which enhanced the dispersion of La2 O3 in the mesopores of OCMK-3. The adsorption capacities of La2 O3 @PCMK-3 and La2 O3 @OCMK-3 increased with the La2 O3 loading amount. Phosphate adsorption onto La2 O3 (14.7)@PCMK-3 followed the pseudo-second-order kinetics with respect to correlation coefficient values (larger than 0.99). As pH increased from 3.4 to 12.0, the phosphate adsorption amounts of La2 O3 (14.7)@PCMK-3 and La2 O3 (15.7)@OCMK-3 decreased from 37.64 mg g −1 and 37.08 mg g −1 to 21.92 mg g −1 and 14.18 mg g −1, respectively. Additionally, La2 O3 @PCMK-3 showed higher adsorption selectivity towards phosphate than coexisting Cl −, NO 3 − and SO 4 2 − . The adsorbent La2 O3 (14.7)@PCMK-3 remained stable after five regeneration cycles.